2017
DOI: 10.1136/bmjopen-2016-012996
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting social influence to magnify population-level behaviour change in maternal and child health: study protocol for a randomised controlled trial of network targeting algorithms in rural Honduras

Abstract: IntroductionDespite global progress on many measures of child health, rates of neonatal mortality remain high in the developing world. Evidence suggests that substantial improvements can be achieved with simple, low-cost interventions within family and community settings, particularly those designed to change knowledge and behaviour at the community level. Using social network analysis to identify structurally influential community members and then targeting them for intervention shows promise for the implemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(55 citation statements)
references
References 53 publications
0
55
0
Order By: Relevance
“…Our study uses full population census data from the western municipalities of the largely rural Copán department of Honduras to analyse the social network determinants of adolescent childbirth at the individual level. Data were collected as part of a randomised controlled trial of social network targeting of a maternal and neonatal health intervention in a study area comprised of 176 villages located in the municipalities of Copán Ruinas, Santa Rita, Cabañas, and San Jerónimo [33,39]. The area was chosen because the villages were geographically diverse, the population experiences high vulnerability to maternal and neonatal health complications, and the location was suitable for data collection.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study uses full population census data from the western municipalities of the largely rural Copán department of Honduras to analyse the social network determinants of adolescent childbirth at the individual level. Data were collected as part of a randomised controlled trial of social network targeting of a maternal and neonatal health intervention in a study area comprised of 176 villages located in the municipalities of Copán Ruinas, Santa Rita, Cabañas, and San Jerónimo [33,39]. The area was chosen because the villages were geographically diverse, the population experiences high vulnerability to maternal and neonatal health complications, and the location was suitable for data collection.…”
Section: Study Populationmentioning
confidence: 99%
“…The area was chosen because the villages were geographically diverse, the population experiences high vulnerability to maternal and neonatal health complications, and the location was suitable for data collection. A full description of the study design and data collection methods is published elsewhere [39]. This part of Honduras also has a traditionally high rate of adolescent fertility [4], making it an ideal study setting for understanding the social dynamics around adolescent childbirth.…”
Section: Study Populationmentioning
confidence: 99%
“…pattern social networks -we should expect social networks to evolve under the pressure of new ideas spreading across them (114).…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…Such algorithms can then be tested in randomized studies to determine whether such non-network-identified seeds are more effective than randomly-or network-selected seeds at reducing HIV risk within the network. More evaluations of SNIs are also required, although such studies can be prohibitively expensive as they require the collection of sociocentric social network data from many independent networks that can then be randomized to different SNIs (115,116).…”
Section: Some Ways Forwardmentioning
confidence: 99%
“…Source: Shakya et al 2017a. reported by a selected respondent (ego) with individuals (alters) they identify in response to the name generator questions. The ties between any ego and alter in the survey are independent of the ties enumerated by other egos, and there is not necessarily any connection between one person's ties and another's.…”
Section: Quantitative Approachesmentioning
confidence: 99%